Integrated finite element models for aeroelastic analysis and piezoelectric energy harvesting in bladeless wind turbines - Kasem, Mohamed Mahran; Elbaz, Ahmed (International Journal of Innovative Research and Scientific Studies, 2025)
Two novel finite element models (FEMs) have been developed to analyze bladeless wind turbines (BWTs): one focusing on aeroelastic analysis and the other on piezoelectric energy harvesting. The aeroelastic model simulates the interaction between aerodynamic loads and the BWT structure, utilizing a semi-empirical wake oscillator model to generate aerodynamic loads while solving the structural equations using FEM. The piezoelectric energy harvesting model predicts the effects of applying sinusoidal aerodynamic loads on the charge generated by piezoelectric patches placed at the root of a plate-like BWT. The aeroelastic model effectively predicts the aeroelastic characteristics of BWTs, providing insights into their stability and performance under various wind conditions. Meanwhile, the piezoelectric energy harvesting model efficiently simulates the energy conversion phenomena, demonstrating the potential for harnessing electrical energy from the mechanical vibrations of BWTs using smart piezoelectric patches that are mounted at the root of a plate-like BWT. These models offer valuable tools for optimizing the design and functionality of BWTs in renewable energy applications.